Analisis Strategi Komunikasi Pemasaran Prabowo Subianto dan Partai Gerindra Melalui Platform TikTok - Sepriyani; Andy Corry Wardhani; Anna Gustina Zainal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Social media has evolved into a crucial nexus for political promotion and communication during the 2024 General Election in Indonesia. This scholarly investigation undertakes an analysis of the digital marketing communication strategies employed by Prabowo Subianto and the Gerindra Party through the TikTok platform. The central focus lies on elucidating the strategic utilization of digital content to cultivate a specific political image and enhance audience engagement, particularly among younger demographics. Employing a descriptive qualitative research methodology, this study incorporates content analysis, observational techniques, and a review of pertinent academic literature. The findings reveal that the Gerindra Party strategically leverages the affordances of TikTok, such as short-form video, prevalent musical trends, and emergent platform trends, to disseminate political messaging in a simplified yet appealing manner. The deployment of creative and dynamic digital content demonstrates efficacy in fostering a positive candidate and party image, concurrently amplifying interaction with younger segments of the electorate. Nevertheless, this research also identifies salient challenges, notably the potential for the propagation of disinformation and the imperative for maintaining rhetorical consistency across digital communications. The scholarly implications of this study contribute valuable insights into the efficacy of the TikTok platform within the realm of modern political communication and underscore the exigency for the strategic adaptation of digital marketing paradigms within the electoral context.